Pattern of recurrence in patients with a pathologically complete response after neoadjuvant chemoradiotherapy and surgery for oesophageal cancer. Issue 2 (20th April 2021) - de Jongh, M; Eyck, B M; van der Werf, L R; Toxopeus, E L A; van Lanschot, J J B; Lagarde, S M; van der Gaast, A; Nuyttens, J; Wijnhoven, B P L
Abstract: Background: Neoadjuvant chemoradiotherapy (nCRT) and surgery is a widely used treatment for locally advanced resectable oesophageal cancer, with 20–50 per cent of patients having a pathological complete response (pCR). Disease, however, still recurs in 20–30 per cent of these patients. The aim of this study was to assess the pattern of recurrence in patients with a pCR after nCRT and surgery. Methods: All patients with a pCR after nCRT and surgery included in the phase II and III CROSS (ChemoRadiotherapy for Oesophageal followed by Surgery Study) trials (April 2001 to December 2008) and after the CROSS trials (September 2009 to October 2017) were identified. The site of recurrence was compared with the applied radiation and surgical fields. Outcomes were median time to recurrence, and overall and progression-free survival. Results: A total of 141 patients with a median follow-up of 100 (i.q.r. 64–134) months were included. Some 29 of 141 patients (20, 6 per cent) developed recurrence. Of these, four had isolated locoregional recurrence, 15 had distant recurrence only, and ten had both locoregional and distant recurrence. Among the 14 patients with locoregional recurrences, five had recurrence within the radiation field, seven outside the radiation field, and two at the border. Median time to recurrence was 24 (10–62) months. The 5-year overall survival rate was 74 per cent and the recurrence-free survival rate was 70 per cent. Conclusion: Despite good overall survival, recurrence still occurred in 21 per cent of patients. Most recurrences were distant, outside the radiation and surgical fields. Abstract : Although patients with a pathological complete response after neoadjuvant chemoradiotherapy and surgery have a good prognosis, recurrence still develops in 21 per cent. Most recurrences were either distant or located outside the radiation and surgical field, which stresses the need for more effective systemic therapy.